2016
DOI: 10.1159/000450786
|View full text |Cite
|
Sign up to set email alerts
|

There's More than Meets the Eye: Complex Associations of Daily Pain, Physical Symptoms, and Self-Efficacy with Activity in Middle and Older Adulthood

Abstract: Background: Participation in activities is associated with a range of positive outcomes in adulthood. Research has shown that pain and physical symptoms are associated with less activity in older adults, whereas higher self-efficacy is associated with more activity. Such research tends to examine cross-sectional or long-term between-person change, limiting the opportunity to explore dynamic within-person processes that unfold over shorter time periods. Objectives: This study aimed to (1) replicate previous bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(27 citation statements)
references
References 41 publications
0
27
0
Order By: Relevance
“…Previous research has primarily focused on the frequency of specific situations (e.g., M. M. Baltes et al, 1990;Wrzus et al, 2016), but not on the diversity across situation types. Such a variable-centered approach, that is, examining the frequency people engage in specific activities, for example, hours or percentage working, hours or percentage religious activities (e.g., Curtis, Windsor, Mogle, & Bielak, 2017;Kahneman, Krueger, Schkade, Schwarz, & Stone, 2004), addresses a very different question compared with examining diversity across several variables, that is, the composition of activities within the day or within the week of a person. In addition, research in other areas such as affective variability or control diversity has shown that indices of diversity uniquely predict mental and physical health over and above mean levels (e.g., Benson et al, 2018;Drewelies, Koffer, Ram, Almeida, & Gerstorf, 2019;Kuppens et al, 2012).…”
mentioning
confidence: 99%
“…Previous research has primarily focused on the frequency of specific situations (e.g., M. M. Baltes et al, 1990;Wrzus et al, 2016), but not on the diversity across situation types. Such a variable-centered approach, that is, examining the frequency people engage in specific activities, for example, hours or percentage working, hours or percentage religious activities (e.g., Curtis, Windsor, Mogle, & Bielak, 2017;Kahneman, Krueger, Schkade, Schwarz, & Stone, 2004), addresses a very different question compared with examining diversity across several variables, that is, the composition of activities within the day or within the week of a person. In addition, research in other areas such as affective variability or control diversity has shown that indices of diversity uniquely predict mental and physical health over and above mean levels (e.g., Benson et al, 2018;Drewelies, Koffer, Ram, Almeida, & Gerstorf, 2019;Kuppens et al, 2012).…”
mentioning
confidence: 99%
“…Data from two samples, the Activity Characteristics and Cognition (ACC) study [6] and the TRAnsitions In Later Life (TRAILLs) study [25] were used to assess our research questions. Both samples were used to assess the first question investigating differences in self-reported leisure activity information based on the assessment time frame.…”
Section: Methodsmentioning
confidence: 99%
“…The activity assessment included items adapted from the National Study of Daily Experiences [22] and preliminary versions of the Activity Characteristics Questionnaire [6,25]. At baseline (weekly estimate), participants were asked to estimate the amount of time they spent in a typical week participating in 28 different activities.…”
Section: Traills Studymentioning
confidence: 99%
“…One interesting question might be what accounts for inter-individual differences in these couplings. In developmental research, age has been one candidate that has often been linked with inter-individual differences in the within-person coupling of diverse variables, for example between daily pain and social as well as physical activities [19], or between the use of memory strategies and performance in an associative recall test [20]. For the stress-NA coupling, a potential correlate is the personality trait neuroticism.…”
Section: Heterogeneitymentioning
confidence: 99%